ATUQ. Quechua stories from Laraos, Lincha, Huangáscar and Madeá, Yauyos province - Taylor, Gerald (1987)
Among the various problems associated with multilingualism in Peru, one of the least studied is that of the dialectal variants spoken by small groups of people who, because they are isolated and do not enjoy national prestige, are threatened with extinction. It is legitimate to wonder if, in this case, its study may have another interest than the strictly scientific one. It seems to us that the language is closely associated with the cultural survival of the ethnic groups that speak it and that it constitutes the strongest link between the members of a given community. The disappearance of the language frequently causes the loss of a large part of the oral tradition and, consequently, of the collective identity.